The Efforts of Tukuneno Catholic Youth in Overcoming Poverty (Forum Ilmu Sosial, 2020)
This qualitative case study aimed to examine the contribution of Tukuneno Catholic youth in alleviating poverty and unemployment by increasing income through efforts to develop the pig farming sector. Through the development of the sector, it was expected to reduce the number of underprivileged people or distance them from the poverty trap so that it could indirectly help lessen the work of local governments in decreasing poverty. The role of religion through the Catholic Church was highly hoped as a government partner in human resource development so as efforts to solve social problems, especially poverty, can be resolved and have a positive impact on the physical and mental development of the nation and state. The Catholic Church, utilizing the Socio-Economic Development Commission of Atambua Diocese (KPSE-KA), tried to embrace Catholic youth by funding the effort until local potentials could be developed. The results of the study showed that previously unemployed young people now have side income and can open their own businesses thanks to the empowerment training conducted by KPSE-KA